Pengaruh Kompetensi Aparat Pengelola Dana Desa, Komitmen Organisasi Pemerintah Desa dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa - Ni Made Ayu Monika Dewi; I Wayan Sudiana (UNHI Press, 2022)
Village funds namely funds that come from state money given to villages. In the management of funds itself must be used transparently for the benefit of public services. This study has a purpose, namely to examine the effect of the Apparatus Competence, organizational commitment with the use of information technology on the accountability at the village office at the Banjarangkan sub-district. In this study the population is village officials who were directly involved with accountability at village office in Banjarangkan Sub-district with a total of 13 villages totaling 185 officers. The sample was determined using purposive sampling method so that 104 people were obtained and instrument testing, classical assumption testing with multiple linear regression tests, the results of the analysis prove that the competence of the apparatus has a positive effect on the accountability in the village office in the Banjarangkan sub-district. Organizational commitment and use of technology have a positive effect on the accountability at the village office at the Banjarangkan district. It is suggested to the village in Banjarangkan sub-district to make more efforts to invite the community to participate in supervising the use of village funds and village officials to try so that the community gets good information regarding the use of the village fund budget